POLYMORPHISM C(-344)T OF THE ALDOSTERONE SYNTHASE GENE AND ESSENTIAL ARTERIAL HYPERTENSION - O. S. Pavlova; S. E. Ogurtsova; M. M. Liventseva; E. V. Kovsh; Yu. V. Afonin; A. G. Mrochek (Евразийский Кардиологический Журнал)
ABSTRACT Objective. To study the association the aldosterone synthase gene (CYP11B2) C(-344)T polymorphism in ethnic Belarussians with essential hypertension (EH). Materials and methods. Genotyping of polymorphic marker C(-344)T of the CYP11B2 was performed by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) in 585 people (391 patients with EH and 194 subjects with normal or optimal blood pressure (BP)). Results. The prevalence of C(-344)T polymorphism genotypes of the CYP11B2 gene did not differ between the groups of hypertensive patients - CC, CT, TT genotypes were detected in 105 (26.8%), 182 (46.6%), 104 (26.6%), and healthy people - in 48 (24.7%), 97 (50.0%), 49 (25.3%), respectively. There were not obtained differences in the level of BP, grade of EH depending on the mutant allele T polymorphism C(-344)T of the CYP11B2 gene among the group of 208 patients without the antihypertensive treatment. Conclusions. In patients with EH of Belarusian ethnicity it was observed equilibrium distribution of the C (50.1%) and T (49.9%) alleles polymorphism C(-344)T of the CYP11B2 gene. The genetic polymorphism C(-344)T of the gene CYP11B2 was not associated with the development of EH in the groups as well as under or after 45 years and taking into account gender differences. Key words: essential arterial hypertension, aldosterone synthase gene, genetic polymorphism.